2012
DOI: 10.1080/00324728.2012.701660
|View full text |Cite
|
Sign up to set email alerts
|

Birth intervals, postponement, and fertility decline in Africa: A new type of transition?

Abstract: We investigated birth-interval dynamics in 24 African countries using data from 76 Demographic and Health Surveys conducted since 1986. Controlling for selection bias in the birth-history data using the Brass-Juárez method and regression models produced almost identical results. Birth intervals have lengthened in every country examined. This analysis uncovered a distinctive and previously undocumented pattern of childbearing that is prevalent across sub-Saharan Africa. After allowing for time trends in birth-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
114
3
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(133 citation statements)
references
References 28 publications
12
114
3
4
Order By: Relevance
“…The trend is most pronounced in Southern Africa and the largest increases have occurred in South Africa, where the median birth interval is thought to have risen to six years by the late 1990s. In Namibia, Zimbabwe, and Lesotho, intervals stand at approximately 45 months (Moultrie, Sayi, and Timaeus 2012). However, this trend is not restricted to Southern Africa: in Ghana the median birth interval has risen to 40 months.…”
Section: Birth Intervals and Fertility Changementioning
confidence: 99%
See 4 more Smart Citations
“…The trend is most pronounced in Southern Africa and the largest increases have occurred in South Africa, where the median birth interval is thought to have risen to six years by the late 1990s. In Namibia, Zimbabwe, and Lesotho, intervals stand at approximately 45 months (Moultrie, Sayi, and Timaeus 2012). However, this trend is not restricted to Southern Africa: in Ghana the median birth interval has risen to 40 months.…”
Section: Birth Intervals and Fertility Changementioning
confidence: 99%
“…In addition to the large literature that examines declines in total family size (Caldwell and Caldwell 2002;Caldwell, Orubuloye, and Caldwell 1992;Cleland, Onuoha, and Timaeus 1994;Cleland 2001;Cohen 1993;Garenne 2008;Garenne and Joseph 2002;Kirk and Pillet 1998), there is growing evidence of a more novel form of fertility change: the lengthening of birth intervals. It has been shown that birth intervals are now lengthening in a large number of populations across sub-Saharan Africa (Bongaarts and Casterline 2012;Moultrie, Sayi, and Timaeus 2012). During the 1960s and 1970s, median birth intervals across the region stood between 27 and 33 months, which is to be expected of populations where lengthy periods of breastfeeding are the norm.…”
Section: Birth Intervals and Fertility Changementioning
confidence: 99%
See 3 more Smart Citations